Cancer-Associated Thrombosis: Beyond Clinical Practice Guidelines—A Multidisciplinary (SEMI–SEOM–SETH) Expert Consensus - Pachón, Vanessa; Trujillo-Santos, Javier; Domènech, Pere; Gallardo, Enrique; Font, Carmen; González-Porras, José Ramón; Pérez-Segura, Pedro; Maestre, Ana; Mateo, José; Muñoz, Andrés; Peris, María Luisa; Lecumberri, Ramón (TH Open, 2018)
Despite the growing interest and improved knowledge about venous thromboembolism in cancer patients in the last years, there are still many unsolved issues. Due to the limitations of the available literature, evidence-based clinical practice guidelines are not able to give solid recommendations for challenging scenarios often present in the setting of cancer-associated thrombosis (CAT). A multidisciplinary expert panel from three scientific societies—Spanish Society of Internal Medicine (SEMI), Spanish Society of Medical Oncology (SEOM), and Spanish Society Thrombosis and Haemostasis (SETH)—agreed on 12 controversial questions regarding prevention and management of CAT, which were thoroughly reviewed to provide further guidance. The suggestions presented herein may facilitate clinical decisions in specific complex circumstances, until these can be made leaning on reliable scientific evidence.
Keywords: cancer; venous thrombosis; pulmonary embolism; prophylaxis; treatment